Christmas cookie murder - Meier, Leslie (Meier, Leslie. Lucy Stone mystery., 2019)
Petty rivalries and feuds that have long been simmering finally come to a boil, leaving a bad taste in the mouths of many guests, including Lee Cummings who accuses Tucker Whitney of stealing her recipe for low fat, sugar-free cookies. But the icing on the cake is when Tucker is found strangled in her apartment on the following morning.